Factors that Affect the Change of Auditors Decision - بکار, مصطفی; الحاسي, جمعة; سالم, عبدالوهاب (Dirasat in Economics and Business, 2011)
This study was intended to discover those factors which may affect the change of auditors decision in the Business forms. The study was deductive-inductive approach fourteen factors was investigated in the study, which assumed to have an effect on auditor change decision. The sample of the study consists of corporate management and the external auditors. The questions was designed in three aspects. Corporate management, the implementation of audit standards and code of ethics and the auditor offices disrepute and deductive statistics were used to analyze the data and to test the study hypothesis spss program was used .The study results showed they there as agreement between auditors and corporate management that audit work quality and seasons for the change. There was dissident concerning the accounting disclosure. Statistically there were no differences between auditors and corporate management at 5% level of signifycance.